A prospective study to evaluate the utility of Mannheim peritonitis index in predicting prognosis of perforation peritonitis at our tertiary care centre - K. V., Saravanan; Alagarsamy, Gowri Sankar; Sankar, Udhaya (International Surgery Journal, 2017)
Background: This study was aimed to evaluate the validity of Mannheim Peritonitis Index (MPI) in predicting the outcome in patients with perforation peritonitis. Methods: A prospective study was designed for a study period of 2 years, 75 patients who underwent operation for perforation peritonitis were included in the study. Post evaluation done with predesigned proforma, MPI score was calculated and analyzed for each patient who underwent surgery, death being the main outcome measure. The MPI scores were divided into three categories. MPI scores <15 (category 1), 16-25 (category 2), and >25 (category 3). Results: Present study consisted of 60 males and 15 females (male:female ratio of 4:1) with the mean patients age 37.96±17.49 years. 47, 26, and 27 cases belonged to MPI score categories 1, 2, and 3. The dominating source of perforation was small intestinal. The individual parameters of MPI score were assessed against the mortality, age >50 years (P = 0.015), organ failure (P = 0.0001), noncolonic origin of sepsis (P = 0.002), and generalized peritonitis (P = 0.0001) were the factors significantly associated with mortality. The sensitivity of MPI was 92% and specificity was 78% in receiver operating characteristic curves. Conclusions: MPI is an effective tool for prediction of mortality in cases of perforation peritonitis.